2010
DOI: 10.1002/prca.201090090
|View full text |Cite
|
Sign up to set email alerts
|

Application of champedak mannose‐binding lectin in the glycoproteomic profiling of serum samples unmasks reduced expression of alpha‐2 macroglobulin and complement factor B in patients with nasopharyngeal carcinoma

Abstract: The use of lectin affinity chromatography prior to 2‐DE separation forms an alternative method to unmask the expression of targeted glycoproteins of lower abundance in serum samples. Reduced expression of α‐2 macroglobulin (AMG) and complement factor B (CFB) was detected in sera of patients with nasopharyngeal carcinoma (NPC) when pooled serum samples of the patients and those of healthy individuals were subjected to affinity isolation using immobilized champedak mannose‐binding lectin and analyzed by 2‐DE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, previous studies have reported some early predictive biomarkers for NPC, such as heat shock protein 27 (HSP27) (8), cathepsin D and keratin 8 (9), alpha-2 macroglobulin (A2M or AMG) and complement factor B (CFB) (10), as well as Galectin-1 (11). To date, some biomarkers for recurrent disease have also been reported, such as serum amyloid A (SAA) (12) and Epstein-Barr virus (EBV)…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have reported some early predictive biomarkers for NPC, such as heat shock protein 27 (HSP27) (8), cathepsin D and keratin 8 (9), alpha-2 macroglobulin (A2M or AMG) and complement factor B (CFB) (10), as well as Galectin-1 (11). To date, some biomarkers for recurrent disease have also been reported, such as serum amyloid A (SAA) (12) and Epstein-Barr virus (EBV)…”
Section: Introductionmentioning
confidence: 99%
“…In addition, enrichment steps can also be performed to samples, to enable a study of a less complex subproteome. For (29)(30)(31)(32).…”
Section: Biomarker For Bone Tumors From Genomics and Proteomics Studiesmentioning
confidence: 99%